A Case of Multiple Myeloma Presenting With Resistant Hypercalcemia - Zeki Kemeç; Cevat Tüzün (Van Tıp Dergisi, 2022)
48-year-old female patient has no disease other than a history of hypertension. She was brought to our clinic with weakness, back pain, walking difficulty, severe hypercalcemia (17.7 mg/dL) and acute kidney injury. Function tests of the kidney improved with hydration. However, hypercalcemia did not respond to hydration. Although antihypercalcemic treatment protocols such as bisphosphonate, corticosteroid, and calcitonin were tried, hypercalcemia did not regulate. Resistant hypercalcemia was considered. In the etiological analysis of hypercalcemia, multiple myeloma was diagnosed with bone marrow fine needle aspiration examination. Cyclophosphamide-velcade-dexamethasone chemotherapy cure (cyclophosphamide, bortezomib, dexamethasone) was given. Afterwards, the serum calcium level could be regulated. Multiple myeloma is mostly seen in older men. The fact that our case was a young woman and her resistant hyperclaemia make her unique.